¿Peter Pan o Wendy? El imaginario infantil en la literatura contemporánea - Bobadilla Pérez, María (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
In the present study the function of memory and childhood imaginary in contemporary narratives is regarded as a discursive space for the negotiation of identity and the construction of subjectivity. Spanish women writers, such as Carmen Laforet, Carmen Martín Gaite or Mercé Redoreda introduce in their novels protagonists who through their memories appear to idealise their childhood, as Peter Pan or even Wendy herself did, while simultaneously rejecting their own adulthood. For all of them, the transition from childhood to maturity is presented as a biographical element which remains unresolved. Taking into consideration the critical works of Rita Felski or Patricia Meyer Spacks and the new narrative model they introduce, the «Novel of Self Discovery» as opposed to the traditional Bildungsroman, the works of the above mentioned authors will be explored paying special attention to those factors that had an impact on the development of feminine subjectivity during the twentieth century.